(untitled) (Bangladesh Journal of Otorhinolaryngology, 2010)
Polymorphous low grade adenocarcinoma is a slow growing tumor mainly arises in minor salivary glands in oral cavity. The frequency of regional lymph node and distant metastasis are very low in this tumor. Careful examination of histolopathological specimen is necessary as features frequently overlap with that of pleomorphic adenoma and adenoid cystic carcinoma. Local excision is the treatment of this condition. Recurrences and distant metastasis were reported in literature many years after surgery. So, long term regular follow up is required in this group of patients. DOI: 10.3329/bjo.v16i1.5784 Bangladesh J Otorhinolaryngol 2010; 16(1): 66-69